Gloss to the resolution of the Supreme Court of February 15, 2019, III CZP 85/18, Legalis - Rzewuska, Magdalena (The Opole Studies in Administration and Law, 2024)
The publication is devoted to the analysis of the resolution of the Supreme Court of February 15, 2019, III CZP 85/18, in which the court found it inadmissible for parents to purchase real estate for a child under their parental authority without the consent of the guardianship court as a result of concluding a sales contract, also in the case when the finances for the purchase were obtained from a targeted donation made by them.